CURRENT DEVELOPMENT OF SOCIAL WORK EDUCATION IN MALAYSIA: VIEWS OF ITS EDUCATORS - Zuraiju, Siti Nur Edlyn Nadia; Omar, Noralina (The Malaysian Journal of Social Administration, 2020)
Social work educators play a prominent role in delivering quality social work education, which later is crucial in producing efficient social work practitioners. Their views on social work education development are crucial to explain the real situation and suggest the improvement needed. This paper discusses the current development of social work education in Malaysian public universities, from the perspective of its educators. It provides empirical evidence based on a qualitative study that collected its data from an in-depth interview involving 20 social work educators in Malaysian public universities. The findings indicate that most of the social work educators provide positive feedback on the development of social work education where there are increasing in the number of public universities that offering social work programme as well as the total number of social work educators. However, there are few social work educators responded on the opposite side. The issues reported in this paper would provide valuable inputs to the government in enforcing the social legislation for the betterment of social work education in Malaysia as a whole.